Digital twins application in the post-harvest supply chain of fruits and vegetables: A systematic review of the literature - Barrientos Barraza, Rodolfo (2023)
The paper focuses on the use of digital twins as a tool to assist in the management of fruits and vegetables supply chains. Problems such as the perishability of food, the complicated coordination between the different actors in the chain, the lack of traceability of products and the demanding quality requirements for their final consumption are part of a long list of factors that must be considered for the analysis of this work. The methodology used was a systematic review of the literature related to the use of digital twins in supply chains. For this purpose, many papers were collected from the most important databases such as Scopus, Web of Science and Proquest. A total of 59 papers were obtained and used for the writing of this paper. For the analysis of information, the data obtained were categorized into factors and dimensions. The 3 factors identified are: pillars of the perishable food supply chain, technological component and finally organization and coordination of the chain. For the findings section, the VosViewer software was used. It was evidenced that digital twins bring a benefit to each factor mentioned in the study.